(untitled) (Orfeu, 2020)
This article aims to analyze the perspectives involved in the debates between erudite and avant-garde, on the one hand, popular and folklore, on the other, around the politicization of art and nationalization of music in Brazil of the first half of the 20th century, especially from H. J. Koellreutter. Therefore, we compare the perspectives of authors such as T. W. Adorno and Antonio Gramsci, H. J. Koellreutter and Mário de Andrade, resorting to documents of H. J. Koellreutter’s and Mário de Andrade’s archives to understand how the musicalization of Mário de Andrade’s Café, by H. J Koellreutter, is part of the debate on Brazilian musical nationalism.